2021
DOI: 10.3389/fpsyt.2020.581494
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness, Emotion Dysregulation, and Internalizing Symptoms During Coronavirus Disease 2019: A Structural Equation Modeling Approach

Abstract: Background: Our study aimed to test the hypotheses that an increased level of loneliness experienced during coronavirus disease 2019 (COVID-19) confinement was predictive of internalizing symptoms and that this pathway was mediated by emotion dysregulation levels.Methods: To reach this aim, we performed an online longitudinal survey recruiting 1,330 participants at Time 1 (at the beginning of the lockdown) and 308 participants at Time 2 (few days before the end of the lockdown). All filled out a set of questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 81 publications
0
28
1
Order By: Relevance
“…Overall, the increase in the use of phones or webcams and pornography during the restrictions period, compared to before the pandemic, was significantly associated with higher levels of mental distress (Shilo and Mor, 2020a ). Pornography consumption can be seen as a coping mechanism to face stress due to uncertainty and insecurity (Mestre-Bach et al, 2020 ; Velotti et al, 2020 ; Zattoni et al, 2020 ). Nonetheless, pornography consumption or using remote devices for sexual satisfaction were not a predictor of abstaining from casual sex during the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the increase in the use of phones or webcams and pornography during the restrictions period, compared to before the pandemic, was significantly associated with higher levels of mental distress (Shilo and Mor, 2020a ). Pornography consumption can be seen as a coping mechanism to face stress due to uncertainty and insecurity (Mestre-Bach et al, 2020 ; Velotti et al, 2020 ; Zattoni et al, 2020 ). Nonetheless, pornography consumption or using remote devices for sexual satisfaction were not a predictor of abstaining from casual sex during the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Kim, , 1999bY. Kim et al, 2020;Knight et al, 1988;Kong et al, 2015;Kurina et al, 2011;Lamm & Stephan, 1987;Lee & Cagle, 2017;Lukács et al, 2019;Matthews-Ewald & Zullig, 2013;McWhirter, 1990;Nazzal et al, 2018;Neto, 2014;Niu et al, 2018;Oshagan & Allen, 1992;Park et al, 2019;Penning et al, 2014;Pretorius, 1993;Robinson-Whelen et al, 2016;Russell, 1996;Russell et al, 1980;Dan Russell et al, 1978;Saito et al, 2019;Sancho et al, 2020;Shi et al, 2016;Shorey et al, 2019;Solano, 1980;Stancliffe et al, 2014;Stephan et al, 1988;Steptoe et al, 2004;Sun & Chang, 2021;Velotti et al, 2021;Wang et al, 2018;Wang et al, 2001;Wilson et al, 1992;Wittenborn et al, 2020;Wongpakaran et al, 2020;Wu & Yao, 2008;Yu et al, 2020;Zakahi & Duran, 1982;Zarei et al, 2016). The PRISMA flow diagram of the study selection process with reasons for excluding studies is shown in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…The mental state of the Italian population has been severely tested, and multiple studies have found a marked increase in psychological symptoms in the nonclinical population. Furthermore, the incidence of high mortality in Italy has considerably aggravated the situation by perpetuating the traumatic dimension of grieving (Bruno et al, 2020;Forte et al, 2020;Mariani et al, 2020;Castellini et al, 2021;Velotti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%